Pengembangan Media Pembelajaran Interaktif Berbasis Nearpod pada Tema Sungguh Kayanya Negeriku Subtema Pemanfaatan Kekayaan Alam di Indonesia - Rahmawati, Henny Annisa; Anwar, Wawan S; Mirawati, Mira (UNIB Press, 2023)
The purpose of this study was to develop and determine the feasibility interactive learning media using Nearpod application on the theme of my country's rich sub-theme of utilizing natural wealth in Indonesia in elementary schools. This research is a development research with a modified ADDIE development model. This development model consists of analysis, design, development, implementation and evaluation. The results of media expert validation showed a percentage of 97.33% with the category